Discrete Supertetrahedral Tn Chalcogenido Clusters Synthesized in Ionic Liquids: Crystal Structures and Photocatalytic Activity. Issue 11 (20th November 2020) - Peng, Yingchen; Hu, Qianqian; Liu, Yifan; Li, Jianrong; Huang, Xiaoying
Abstract: Discrete supertetrahedral T n chalcogenido clusters, which can be regarded as the smallest semiconductor quantum dots with precise chemical composition, have attracted considerable attention due to their outstanding photoluminescent, photoelectric, and photo/electrocatalytic properties. Such discrete molecular clusters are suitable for solution processing towards functional materials and can be used as precursors for constructing open‐framework chalcogenides. Traditionally they were synthesized hydro(solvo)thermally with molecular solvents (e. g. water or organic amines), while until recently imidazolium‐based ionic liquids (ILs) were found suitable for their preparation acting as reactive solvent and stabilizer for molecular clusters. We discuss herein recent advances in the syntheses, crystal structures, and selected properties of discrete supertetrahedral T n chalcogenido clusters obtained in ILs. In particular, the enhanced photocatalytic properties of monodispersed T n clusters in solvents are highlighted. Abstract : Cluster catalysis : This Minireview concentrates on recent advances in the syntheses, crystal structures, and selected properties of discrete T n chalcogenido clusters synthesized in ionic liquids. The functions that ionic liquids played in the construction of discrete T n clusters are emphasized. Such clusters exhibit adjustable and intriguing properties, in particular enhanced photocatalytic activities by monodispersing T n clusters in solvents are highlighted.